Production and characterization of monoclonal antibodies to cholera toxin. - Remmers, E F (1982)
Monoclonal antibodies against cholera toxin were produced to obtain highly specific antisera to cholera toxin. Fifteen hybridoma cell lines producing monoclonal antibodies specific for the determinants of cholera toxin were derived from the fusion of mouse myeloma cells and spleen cells from mice immunized with cholera toxin. The cell lines were stabilized, examined for specific antibody production, and immortalized by freezing cultured cells and tumor cells which had been grown subcutaneously in mice. All cell lines continued antibody secretion upon thawing. The antibodies produced by the hybridoma cell lines were characterized by determination of the class of light- and heavy-chain components and by determination of specificity for the cholera toxin subunit. All of the antibodies contained the k light chain, 4 contained the mu heavy chain, and the remaining 11 contained the gamma 1 heavy chain. Ten of the monoclonal antibodies are specific for the B subunit of cholera toxin, and three are specific for the A subunit. The remaining two appear to react with both subunits.